Fungal degradation of bamboo treated with crude lake salt and a mixture of borax and boric acid - Mwanja, Christine Kalembe; Terziev, Nasko; Ishengoma, Romanus; Banana, Abwoli; Kalanzi, Fred (Elsevier B.V, 2024)
This study compared the effectiveness of crude lake salt, a traditional preservative used by artisans in Uganda, and borax-boric acid, a conventional preservative, against fungal degradation. Using the European standard, an experiment was set up to determine the durability of Oxytenanthera abyssinica, Oldeania alpina and Bambusa vulgaris treated with 2 % and 6 % crude lake salt and borax-boric acid against Gloeophyllum trabeum, Coniophora puteana and Trametes versicolor. Mass loss comparisons between treated and untreated bamboo samples were made. Durability classes were assigned according to the amount of mass lost. Bamboo samples exposed to G. trabeum had lower surface hyphal coverage compared to those exposed to C. puteana and T. versicolor irrespective of the preservative used. Samples treated with borax-boric acid were in durability class I compared to those treated with crude lake salt that were between class II and III according to European standard. The lowest mass loss for bamboo treated with crude lake salt was 5.9 % in O. abyssinica exposed to G. trabeum. The highest mass loss for bamboo treated with crude lake salt was 14.24 % in B. vulgaris exposed to T. Versicolor. The study confirmed that while artisans use crude lake salt as a traditional preservative, it does not protect against white and brown rot while all concentrations of borax-boric acid provided protection against all fungi.